2016
DOI: 10.1111/os.12239
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Diagnosis and Its Effect on Clinical Outcome in High‐grade Sarcoma of Bone: A Referral Oncological Centre Study

Abstract: Prolonged delay in diagnosis does not result in lower survival. Metastatic disease has a pronounced effect on survival. Aggressive tumor behavior results in shorter delays. Minimizing GP-related delays could be achieved by adopting a lower threshold for obtaining plain radiographs at the pre-hospital stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…This study focused on the potential impact of two time intervals on the survival of children diagnosed with osteosarcoma who were treated in an LMIC. Our findings reveal that the median LD was longer than that observed in HIC and was comparable to reported times in other LMIC . Initial metastatic disease was found in 42.4% of patients; however, we failed to associate this finding with a delayed LD, which is similar to published data .…”
Section: Discussionsupporting
confidence: 87%
“…This study focused on the potential impact of two time intervals on the survival of children diagnosed with osteosarcoma who were treated in an LMIC. Our findings reveal that the median LD was longer than that observed in HIC and was comparable to reported times in other LMIC . Initial metastatic disease was found in 42.4% of patients; however, we failed to associate this finding with a delayed LD, which is similar to published data .…”
Section: Discussionsupporting
confidence: 87%
“…Thirty-four studies involving a total of 17 258 patients investigated the total interval in BS (table 1)8–41; five of these studies prospectively collected follow-up data. A broad range in the length of the total interval was found, which varied from 9 to 120.4 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Tumour histology was found to be of influence on the total interval. Goedhart et al performed a retrospective study among 102 patients with high-grade BS and reported a significantly longer patient interval and secondary care interval for chondrosarcoma versus Ewing sarcoma and osteosarcoma,21 which resulted in a significantly longer total interval, with a mean of 98.3 weeks for chondrosarcoma, versus 22.9 and 23.3 weeks for Ewing sarcoma and osteosarcoma, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Osteosarcoma (OS) is the most common primary malignant bone tumour among adolescents and young adults (1) and has a high metastatic rate and poor prognosis. With advances in the treatment modality for OS, such as chemotherapy or surgery combined with chemotherapy, the survival of patients with OS has markedly improved in recent years (2), and the 5-year survival rate in patients with non-metastatic OS has reached 60-70% (3). However, the survival of patients with distant metastasis remains poor with the 5-year survival rate rarely reaches 20% (4).…”
Section: Introductionmentioning
confidence: 99%